PERTANGGUNGJAWABAN PIDANA PEMBUAT SERTIFIKAT AKSIN COVID-19 TANPA VAKSINASI - Zeinudin, Moh.; Utamie, R. Aj. Nindya Rizky (Jurnal Jendela Hukum, 2023)
Covid-19 rocked Indonesia in early 2020. In the course of time, Covid-19 has spread to 34 provinces in Indonesia. The member of these cases is increasing every day. Cries of confusion from the people sounded fromall directions. In dealing with this, the Government of Indonesia issued a program that cannot be separated from the pro and con attitudes of the community, namely the vaccination program. Behind this program it turns out that it also gave birth to several “rogue” parties who became the issues of the Covid-19 Vaccine Certificates without going through the vaccination proces either in the form of letters of electronic documents. Some experts have dismissed the issue of this. Things like this are the Government’s homeworks to be throughly investigated and no longer appear in the community.